Comparison of Behavioral Responses to Manual Restraint Tests in Two Breeds of Japanese Native Chicken - Oka, T.; Bungo , T. (International Journal of Poultry Science, 2014)
The aim of the present study was to evaluate the characteristic of two native Japanese chicken breeds, Uzurao (UZ) and Chabo (CB) using two types of manual restraint tests for the detection of fearfulness. Each hen was grabbed by one hand or held in an underarm with mild pressure, whereas the other hand was used to restrain the legs. Thereafter, latencies to the first struggle and frequencies of struggling were recorded. The latency in UZ was shorter than that in CB (p<0.01), but there was no significant difference between restraint types. The frequency of struggling in UZ during arm restraint test was significantly higher than others (p<0.05) but no significant differences were found among others. Between the restraint types, there was a positive correlation (p<0.05) in frequency, but not in latency to struggling (p>0.1). These findings demonstrate that UZ birds may be confirmed to respond less fearfully in fear-eliciting situations than CB birds and further suggest that the temperamental differences may correspond to genetic characteristics of breeds. Additionally, a newly developed technique, arm restraint, is useful to detect fearfulness in chickens, similar to hand restraint.